Educational software for stress analysis of an aircraft fuselage - Mohamed Ali, Jaafar Syed; Mustafa Kamal, Izyan Liyana; Ismail, Nurhuda (2010)
Abstract—A stress analysis software based on MATLAB graphical user interface (GUI) has been developed. The developed software can be used to estimate internal loads on a fuselage and to compute the stresses at any point along the length of the fuselage of a given aircraft. The generalized formulation allows user to perform stress analysis even on tapered fuselages. The software is expected to be a useful tool for effective teaching learning process of courses on aircraft structures and aircraft structural design.